The Dubious Case of a Failed Coup
XI, 246 p. 26 illus.
Keywords: The editors have made sure that this study of politicized masculinities includes authors who are interested in Turkish women's political actions, thus making the analysis of masculinities much more nuanced and useful. This book will be a valuable resource for students and scholars of international relations, gender studies, Turkish studies, and Middle East studies. —Cynthia Enloe, Professor, Clark University, USA Analyses of gender, militarism, films, novels, football, video games and psychoanalytic narratives jostle in the pages of this original volume which goes beyond an analysis of the failed military coup of July 15, 2016, and its continuing aftermath. By engaging frontally with the realm of symbols and symbolism, it gets under the skin of political culture in Turkey and its enduring tropes. —Deniz Kandiyoti, Emeritus Professor, School of Oriental and African Studies, UK This volume is an attempt to contextualise the coup attempt of 15 July 2016 in Turkey, within the framework of militarism and masculinities. The immediate aftermath of the 15 July in Turkey witnessed confusion, contestation and negotiation among different narratives, until a hegemonic version was superimposed on the collective memory as part of official history building. This project is an attempt to bring a fresh and critical perspective by compiling together analyses from various disciplines of political science, media and film studies, literature, sociology and cultural studies. Several chapters of this volume delineate the paradox of “victorious militarism,” meaning that despite the failure of the coup, its aftermath has been shaped by a new wave of state-sponsored gendered militarism, with the establishment of a regime of “state of emergency.” Feride Çiçekoğlu received her PhD in architecture from University of Pennsylvania. She started teaching in Turkey but she was imprisoned during the military junta of 1980 because of her political opposition. She is a professor at İstanbul Bilgi University, Department of Film and Television. Ömer Turan received his PhD from Central European University, Department of Sociology and Social Anthropology. He is an associate professor at İstanbul Bilgi University, Department of International Relations.